COMMUNITY-BASED NONFORMAL ISLAMIC EDUCATION: A STUDY OF THE MOSQUE AND ISLAMIC BOARDING SCHOOL EDUCATION MODELS: Pendidikan Islam Nonformal Berbasis Komunitas: Studi Atas Model Pendidikan Berbasis Masjid Dan Pesantren - Nidauddin fillah; Miswanto miswanto; Miftahul Huda (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Community-based nonformal Islamic education serves as an important educational mechanism outside formal schooling, particularly within mosques and Islamic boarding schools (pesantren). This study aims to analyze and compare community-based nonformal Islamic education models implemented in these two institutions. The research employs a qualitative descriptive-analytical approach, with data collected through in-depth interviews, observations, and document analysis at Roudlotus Salam Mosque and Mambaus Sholihin Islamic Boarding School.The findings reveal that both mosque- and pesantren-based nonformal Islamic education depend on strong community involvement. Nevertheless, they exhibit different pedagogical orientations. Mosque-based education is characterized by openness, flexibility, and adaptability to community needs, enabling inclusive participation across age groups and social backgrounds. Meanwhile, pesantren-based education is more structured and rooted in classical Islamic traditions, utilizing methods such as bandongan, sorogan, and muhafadzoh to transmit religious knowledge, scholarly lineage, and moral values. The novelty of this research lies in its comparative mapping of parallel education models in mosques and pesantren. The study demonstrates that community-based nonformal Islamic education is not monolithic but varies according to institutional structure, pedagogical tradition, and social context, thereby enriching contemporary discourse on Islamic education models.